PENGEMBANGAN MODUL BERWAWASAN LINGKUNGAN DALAM RANGKA MENINGKATKAN PENGETAHUAN DAN MORAL LINGKUNGAN SISWA SD DI DAERAH INDUSTRI, KOTA, PANTAI DAN DESA - Bambang Gonggo Murcitro (Perspektif Ilmu Pendidikan, 2006)
This research is directed to create enviromental friendly moduls that can be used for improving knowledge and moral of elememtary student enviromentals in industrial areas, cities, beach and farming areas. The research was condusted on 150 elementary students of the sixth grade selected with cluster random sampling. The research resulth showed that: 1) The moduls could be em ployed to increase the knowledge of elementary students about enviroments in industrial areas, beach, cities and farming areas. Through the testing of the hypothesis on the student knowledge data using Anacova test, it was obtained the calculated F as big as 1.98 that less than the table F value 2.68. 2) Enviromental friendly moduls can be utilized to increase the moral of elementary student concerning environments industrial areas, beach, cities and forming areas. Though the hypothesis testing uses Anacova to the data of student moral about enviromental, it was obtaind that a the calculated F value as great as 0.31 that means lesses than the table F value of 2. 68.